Pengaruh Keselamatan dan Kesehatan Kerja (K3) Terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening: Studi pada Karyawan PT. Kaltim Prima Coal - Marshya Daffa Sayuda; Edy Raharja (Faculty of Economics and Business Diponegoro University, 2025)
This study aims to examine the effect of occupational safety and health (OSH) on employee performance with job satisfaction as a mediating variable at PT Kaltim Prima Coal.The population in this study consists of 120 employees, with a sample of 75 permanent employees selected using the census method. Data were collected through questionnaires measured using a five-point Likert scale. The analysis was conducted using Structural Equation Modeling (SEM) with the assistance of SmartPLS version 4.1.0.9.The results show that occupational safety and health has a positive and significant effect on employee performance. In addition, job satisfaction plays a mediating role in the relationship between occupational safety and health and employee performance.